A flexible intestinal anastomosis stent
By designing an intestinal flexible anastomosis scaffold based on P(TMC-co-PDO) copolymer and bioflex elastomer materials of PLA, PCL, and PBS, the problem of non-biodegradability and poor mechanical matching of traditional staplers is solved, and the effect of effectively isolating intestinal contents and promoting healing is achieved.
Patent Information
- Application Number
- CN202111173424.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-10-08
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2041-10-08
AI Technical Summary
The prior art cannot effectively prevent and treat anastomotic fistula in gastrointestinal reconstruction anastomosis, and traditional staplers are not biodegradable, have poor mechanical matching, and cannot reasonably regulate intestinal function.
A flexible intestinal stent was designed, adopting a tubular stent body, with the upper and lower ends of the stent being the inlet end and the outlet end respectively, and the outlet end was provided with a concave polygonal structure and an inward folding pleated structure. The material of the stent was based on P(TMC-co-PDO) copolymer and bioflex elastomer based on PLA, PCL, and PBS.
This anastomosis stent can effectively isolate intestinal contents, reduce the probability of anastomosis fistula and other complications, and the material can be biodegradable, and its mechanical properties match intestinal tissue, promoting healing and functional recovery.
Smart Images

Figure CN113855134B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of gastrointestinal reconstruction anastomosis instruments, and in particular to an intestinal flexible anastomosis bracket. Background Art
[0002] Gastrointestinal reconstruction anastomosis is one of the most common surgical procedures in abdominal surgery. In the nearly one century of development of gastrointestinal surgery, the incidence of anastomotic fistula has not decreased significantly, and has always been one of the world's problems that plague the success rate of gastrointestinal surgery. Intestinal lesions such as benign and malignant gastrointestinal tumors, gastrointestinal perforation, gastrointestinal obstruction, bleeding, ischemia, etc. often require resection of part of the diseased intestine before anastomosis. Traditional methods are mostly manual suture anastomosis. In recent decades, tubular staplers have been used for end-to-end or end-to-side anastomosis, or linear cutting closure devices have been used for side-to-side anastomosis. Regardless of the anastomosis method, it is impossible to prevent and treat anastomotic fistula, a fatal complication.
[0003] At present, temporary diversion surgery, such as temporary ileostomy or colostomy, is generally accepted and practiced by colorectal surgeons at home and abroad. Such additional surgery can definitely avoid complications caused by anastomotic leakage, but there is no literature to support whether it can reduce the probability of anastomotic leakage. However, diversion surgery requires a planned secondary surgical reduction, which also means another digestive tract reconstruction and anastomosis. There is also a probability of related complications such as anastomotic leakage and anastomotic stenosis, but the probability is lower than that of the first surgery. Under the condition of good blood supply at both ends of the anastomosis and no tension on the anastomosis, the isolation of intestinal contents, especially fecal contents, in the anastomotic area and the realization of a relatively isolated and clean local environment are effective strategies to prevent anastomotic leakage and complications such as peritonitis and abdominal abscess. The key technical bottleneck for the realization of this strategy is the breakthrough of ideal auxiliary anastomotic materials. The purpose of intestinal anastomosis is to restore the physical, histological and physiological functions of the intestines at both ends of the anastomosis. At present, the main problems with traditional staplers include: (1) Metal staplers are not biodegradable, resulting in permanent retention in the body; (2) Degradable polymer staplers lack mechanical compatibility with wound tissue; (3) Staplers do not have tissue repair regulation functions and cannot reasonably regulate the restoration of normal intestinal function.
[0004] Clinically, the implementation of all intestinal anastomosis consists of the following steps: good preoperative preparation, appropriate surgical timing, scientific anastomosis (surgical) method and meticulous postoperative management. Among them, the scientific anastomosis method is the most important because it is directly related to the success or failure of the operation. [9]In theory, a scientific anastomosis method should have the following characteristics: (1) The anastomosis effect is reliable, and the intestinal healing process after anastomosis is consistent with its injury and repair process under physiological conditions, with neither insufficient healing (anastomotic leakage) nor excessive healing (scar fibrosis, anastomotic stenosis); (2) The operation itself causes little damage to the intestinal wall tissue at both ends of the anastomosis, and the early anastomotic connection materials (sutures, metal nails, etc.) required for the operation cause a slight foreign body reaction in the body and disappear on their own after healing is completed (excreted from the body or degraded in the body); (3) The operation is simple and easy to perform, with strong scalability and a short learning curve; (4) The operation is highly versatile and can be used in a variety of surgical conditions, such as different surgical sites (small intestine, colorectal, etc.), different anastomosis methods (end-to-end, end-to-side, etc.) and different surgical timings (emergency or elective surgery), and can even be used in complex systemic or local abdominal conditions such as abdominal infection, chemotherapy, and malnutrition.
[0005] Many research centers at home and abroad are conducting research on various types of gastrointestinal "intraluminal support" anastomosis, in which the support carriers are mainly various artificially synthesized new polymer biodegradable materials. For example, Detweiler MB et al. used a sliding biodegradable stent SAINT (sliding absorbable intraluminal nontoxic stent) to complete intestinal anastomosis; Buch N et al. used a fast-degrading (<2 hours) polymer stent prosthesis (Polyglycols@Hoechst SBStube) on the basis of conventional single-layer surgical colon anastomosis, which can improve the mucosalepithelial covering of the anastomotic mucosa and tissue oxygen partial pressure; Tsereteli Z et al. used the polyester PolyflexTM stent in an animal model of anastomotic leakage after colon surgery, proving that the PolynexTM stent can reduce postoperative complications and promote the healing of anastomotic leakage; the "C-sealTM" invented by the Dutch Polyganics BV company is also a biodegradable polymer material. Combined with the stapler operation, it can reduce the incidence of anastomotic leakage in low-position colorectal surgery.
[0006] The "intraluminal support method" has not only been successful in the field of surgical intestinal anastomosis, but also performed well in digestive endoscopy. The self-expanding metallic stent (SEMS) is the most common representative of the "intraluminal support method" under endoscopy. People can not only use its internal support function to treat gastrointestinal stenosis (or obstruction) diseases, but SEMS has also been repeatedly proven to be used to treat surgical diseases such as gastrointestinal perforation and anastomotic fistula that originally required surgical treatment, although it is currently limited to selected cases. In 2009, Amrani L et al. proposed the concept of "stent-guided regeneration and re-epithelialization". He pointed out that the stent can divert and isolate the contents of the digestive tract, so that the site to be healed (anastomosis or injury site) can heal in an "undisturbed" environment. In addition, the stent can also provide a platform for epithelial cells to crawl during the healing process, promoting "re-epithelialization". In recent years, "endoluminal vacuum therapy" (EVT) has been proposed in endoscopy. Its concept is similar to that of intraluminal stents, that is, using a "sponge-like" intraluminal implant that can be externally connected to negative pressure drainage to drain the intestinal contents around the site to be healed out of the body, so that the anastomosis can be healed under lower pressure and relatively dry conditions.
[0007] The domestic patent situation of related intestinal repair devices is as follows: Invention patent CN 111449707A proposes an anorectal stapler, including a handle seat, a transmission assembly, a firing assembly and a kissing assembly; the transmission assembly includes a screw rod arranged inside the handle seat and an adjustment mechanism arranged at the tail end of the handle seat and connected to the tail end of the screw rod; a nail support seat is fixedly installed at the front end of the screw rod; the firing assembly includes a movable handle arranged on the handle seat and a straight push rod sleeved on the screw rod; the kissing assembly includes a nail pusher, a nail magazine sleeve, a nail magazine and a ring knife. In this invention, the nail pusher, the nail magazine sleeve and the nail magazine are all made of metal materials. The parts cannot be degraded in the body and can only be permanently retained in the body or removed by secondary surgery. Patent CN109480943A is made of degradable materials, and adopts the method of fixing the nail body by perforation, and a support frame is designed at the rear end of the nail body, but the anastomotic ring is hard and inelastic, and cannot adapt well to intestinal peristalsis, and the foreign body sensation is obvious. Similar invention patent CN103230265A uses biodegradable materials such as polyglycolide and polylactide as raw materials for gastrointestinal anastomosis. The stapler has the function of being easily broken, but it also lacks mechanical compatibility with intestinal tissue. An ideal stapler should have the following characteristics: (1) effectively isolate intestinal contents; (2) cause little damage to the intestinal wall of the anastomosis during the stapler implantation operation; (3) be simple and easy to operate. Currently, no anastomotic device on the market can meet the above requirements at the same time.
[0008] Based on all the above-mentioned application problems in endoscopic and surgical practice, we can conclude that intracavitary isolation and intracavitary decompression can promote intestinal healing, so that ideal healing can be safely achieved in high-risk situations such as gastrointestinal perforation and anastomotic fistula. In fact, surgeons should be familiar with this conclusion. For example, the common gastrointestinal decompression and intestinal stoma diversion in clinical work are the application of "intracavitary isolation and intracavitary decompression". The "intracavitary support method" is similar to the use of certain polymer materials to transform the traditional gastrointestinal "decompression + external drainage" into "support + internal drainage", which greatly improves the patient's quality of life; and the implant can degrade itself after completing its function and does not remain in the body. Summary of the invention
[0009] In order to solve the technical defects of the prior art, the present invention provides an intestinal flexible anastomosis stent.
[0010] The technical solution adopted by the present invention is: an intestinal flexible anastomotic stent, including a tubular stent body, the stent body including a side wall, the upper and lower ends of the stent body are respectively an inlet end and an outlet end, a boss is provided on the annular upper edge of the inlet end, the lower edge of the outlet end is a concave polygonal structure, each dominant angle of the lower edge of the concave polygonal structure forms an inwardly folded pleated structure on the side wall of the stent body, and the lower edge of the concave polygonal structure is deformed under force to reduce the angle of the dominant angle.
[0011] The support body comprises a suture portion, and the suture portion comprises a ring-shaped upper edge at the inlet end and a non-dominant angle edge of a lower edge of a concave polygonal structure at the outlet end.
[0012] The length of the pleated structure is 1 / 2-2 / 3 of the height of the bracket body.
[0013] The thickness of the inner wall of the bracket body is 0.20-0.6 mm.
[0014] The thickness of the side wall of the intestinal anastomosis stent at the fold structure is smaller than the thickness of the side wall above the fold structure.
[0015] The pleated structure is an arc-shaped groove structure that is shallow at the top and deep at the bottom, and the deepest depth of the bottom of the arc-shaped groove is 0.4-0.8mm.
[0016] The stent body is made of a bio-flexible elastomer, which is a blend of a P (TMC-co-PDO) copolymer and at least one of PLA, PCL, and PBS. The addition ratio of TMC and PDO in the P (TMC-co-PDO) copolymer is 9:1 to 6:4, and the blending ratio of at least one of PLA, PCL, and PBS is 5 to 20%.
[0017] The intestinal flexible anastomotic stent is prepared by the following steps:
[0018] (1) Synthesis of P(TMC-co-PDO) copolymer: In an environment without water and oxygen, 90-60wt% TMC monomer, 10-40wt% PDO and 1-5wt% catalyst Sn(Oct)2 solution are added to a reaction tube, a magnet is placed in the reaction tube to ensure that the reaction tube is free of water and oxygen, the tube mouth is sealed with silicone grease to ensure that no oxygen and water enter, the reaction tube is placed in an oil bath pot for reaction at a temperature of 120-150°C for a reaction time of 24-48h, and after the reaction is completed, the tube is taken out for use;
[0019] (2) Dissolution of P(TMC-co-PDO): Dissolve the P(TMC-co-PDO) copolymer with CHCl3, DMF or THF at a solid-liquid ratio of 1:5. First, wash the inner wall with CHCl3, DMF or THF several times to wash away the silicone grease and unreacted monomers. Then, add excess CHCl3, DMF or THF and place on a shaker with the shaker temperature set at 37°C until the solution is completely dissolved.
[0020] (3) Purification of P(TMC-co-PDO): The dissolved solution was slowly poured into a beaker filled with n-hexane for purification. The mixture was slowly poured in and stirred continuously. The obtained flocculent P(TMC-co-PDO) was filtered and then vacuum dried for 48 h.
[0021] (4) Preparation of electrospinning solution: P(TMC-co-PDO) copolymer and at least one of PLA, PCL and PBS were compounded, added to the solvent DMF / THF, wherein DMF:THF=1:1, and placed in a constant temperature shaker at 37°C for 24 hours until completely dissolved, and then electrospinning was performed after complete dissolution;
[0022] (5) Preparation of anastomotic tube by electrospinning: The intestinal flexible anastomotic stent according to any one of claims 1 to 7 is obtained by electrospinning on an electrospinning device, and the parameter setting range is as follows: voltage (-5, 30) V; needle push speed V = 1.0 ~ 5.0 ml / h; roller speed V = 100 ~ 500 RMP; temperature T = 25 ~ 35 ° C; humidity WET = 20 ~ 40%.
[0023] The beneficial effects of the present invention are as follows: the present invention provides an intestinal flexible anastomotic stent, which has a three-dimensional mesh micro-nano structure that matches the elasticity of the intestine. The lower edge of the outlet end of the stent body is a concave polygonal structure. Each dominant angle of the lower edge of the concave polygonal structure forms an inwardly folded pleated structure on the side wall of the stent body. The pleated structure can also accommodate secretions from the inner wall of the intestine and the suture. The lower edge of the concave polygonal structure is deformed by the force of the intestinal contents to reduce the angle of the dominant angle, thereby discharging the secretions in the pleated structure downward along the pleated direction, significantly reducing the probability of intestinal anastomotic fistula and other complications. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 It is a schematic diagram of the structure of the present invention.
[0025] Figure 2 It is a three-dimensional diagram of the structure of the present invention.
[0026] Figure 3 It is a schematic diagram of the lower edge structure of the outlet end of the support body of the present invention.
[0027] Figure 4 The SEM images of the P(TMC-co-PDO) random copolymer electrospun scaffolds with different monomer addition ratios are shown in Figure 1. 1-scaffold body, 2-boss, 3-reflex angle, 11-inlet end, 12-outlet end, and 31-pleated structure. DETAILED DESCRIPTION
[0028] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0029] Material composition:
[0030] A bio-flexible elastomeric intestinal anastomosis stent based on a blend of P (TMC-co-PDO) copolymer and at least one of PLA, PCL, and PBS. The intestinal anastomosis stent is made of P (TMC-co-PDO) copolymer material as a whole, and is blended with at least one of PLA, PCL, and PBS. The P (TMC-co-PDO) copolymer is a random copolymer P (TMC-co-PDO) synthesized by ring-opening polymerization of polymer medical materials TMC and PDO. The addition ratio of TMC and PDO in the P (TMC-co-PDO) copolymer is 9:1 to 6:4, the blending ratio of at least one of PLA, PCL, and PBS is 5 to 20%, and the thickness of the intestinal anastomosis stent is 0.4-0.8 mm.
[0031] Manufacturing process:
[0032] Electrospinning: Preparation of electrospinning solution: The mass fraction of the solution is 5-10%, and the solvent is DMF / THF=1 / 1 (V / V). P(TMC-co-PDO) copolymer and at least one of PLA, PCL, and PBS are compounded, added to the solvent, and placed in a 37°C constant temperature shaker for 24 hours until completely dissolved. The dissolved electrospinning solution is electrospun. Electrospinning conditions: voltage (-5, 30) V; needle push speed V=1.0~5.0 ml / h; roller speed V=100~500 RMP; temperature T=25~35°C; humidity WET=20~40%.
[0033] The specific preparation method is as follows:
[0034] 1. Synthesis of P (TMC-co-PDO) copolymer: The synthesis process needs to be carried out in an environment without water and oxygen. 90-60wt% TMC monomer, 10-40wt% PDO and 1-5wt% catalyst Sn (Oct) 2 solution are added to the reaction tube. A magnet is placed in the reaction tube to ensure that the reaction tube is free of water and oxygen. The tube mouth is sealed with silicone grease, and finally the tube mouth is sealed with a sealing film to ensure that no oxygen and water enter. The reaction tube is placed in an oil bath pot for reaction at a temperature of 120-150°C for 24-48 hours. After the reaction is completed, it is taken out for use.
[0035] 2. Dissolution of P(TMC-co-PDO): Dissolve the synthetic material with CHCl3, DMF or THF at a solid-liquid ratio of 1:5. First, wash the inner wall with CHCl3, DMF or THF several times to wash away the silicone grease and unreacted monomers, then add excess CHCl3, DMF or THF, place on a shaker, set the shaker temperature to 37°C, and wait for the solution to completely dissolve.
[0036] 3. Purification of P(TMC-co-PDO): Slowly pour the dissolved solution into a beaker filled with n-hexane for purification, slowly pour in and stir continuously with a glass rod. Filter the obtained flocculent P(TMC-co-PDO) and then place it in a vacuum drying oven to dry for 48 hours.
[0037] 4. Preparation of electrospinning solution: The substances used are dissolved in the solvent DMF / THF (DMF:THF=1:1), and the mass fraction of the solution is 5-10wt%. Among them, P(TMC-co-PDO) copolymer and at least one of PLA, PCL, and PBS are compounded, added to the solvent DMF / THF (DMF:THF=1:1), and placed in a constant temperature shaker at 37°C for 24 hours until completely dissolved. After complete dissolution, the electrospinning operation is carried out.
[0038] 5. Preparation of anastomosis tube by electrospinning: Spinning was performed on an electrospinning machine of model TL-Pro-BM. The parameter setting range is as follows: voltage (-5, 30) V; needle push speed V = 1.0 ~ 5.0 ml / h; roller speed V = 100 ~ 500 RMP; temperature T = 25 ~ 35 ° C; humidity WET = 20 ~ 40%.
[0039] Table 1. Electrospinning conditions
[0040]
[0041] Table 2. Composition and physical properties of P(TMC-co-PDO) copolymers
[0042]
[0043] For random copolymers with different monomer ratios, their degradation rates and mechanical properties vary greatly, and different monomers and different feed ratios will also have a certain effect on the molecular weight of random copolymers. Implantation in the intestine requires the product to have a suitable degradation rate and excellent mechanical properties. Therefore, this experiment focuses on the effect of different ratios of TMC monomer to PDO in the raw material on the molecular weight and physical properties of the random copolymer P (TMC-co-PDO). The factor of different mass ratios of TMC and PDO monomers in the raw material was studied, and the reaction time was controlled to 24h. The results are shown in Table 2. The data show that as the proportion of PDO in the raw material increases, the intrinsic viscosity of P (TMC-co-PDO) decreases as the molecular weight decreases, while the degree of molecular weight reduction is small.
[0044] The good hydrophilicity of the material makes it more biocompatible. Therefore, in order to evaluate the hydrophilicity and hydrophobicity of P(TMC-co-PDO), the water contact angle on the sample surface was measured by a dynamic contact angle experiment and is listed in Table 3. The results clearly show that with the increase in the proportion of PDO monomer added in the copolymer, there is no obvious difference in the dynamic contact angle at the beginning, which shows that the random copolymer has a more obvious hydrophobicity. However, as time goes on, the water contact angle on the sample surface is measured every five minutes. The contact angle of all samples decreases with time, including the hydrophobic samples, indicating that the loose porous structure of electrospinning allows water to enter the interior of the material through the gaps, and the higher the proportion of PDO polymerized monomers, the greater the rate of change of the contact angle, that is, the greater the porosity. The change in the gap can be demonstrated from the electron microscope photos of the material. As Figure 1 As shown in the figure, the scanning electron microscope was used to test the microstructure of the spinning material of the random copolymer P (TMC-co-PDO), and it was found that with the increase of PDO, the fiber structure of the electrospun material showed a trend of gradually increasing porosity.
[0045] Table 3. Hydrophilicity and mechanical properties of P(TMC-co-PDO) random copolymer electrospun scaffolds with different monomer addition ratios
[0046]
[0047] The random copolymers obtained by the addition ratio of TMC and PDO monomers have different block distributions, which also has a great influence on the mechanical properties of the material. The mechanical properties of the anastomosis stent prepared by P (TMC-co-PDO) electrospinning are listed in Table 3. With the increase of the PDO monomer ratio, the tensile strength of the electrospun membrane of the random copolymer increased from 16.53MPa to 26.79MPa. This is because with the increase of PDO, the PPDO segment in the copolymer increases, and its tensile strength is stronger than that of pure PTMC material, so the tensile strength is enhanced.
[0048] Based on the requirements of the environment in which the material is used, it is located in the rectum, the material needs to maintain a certain hydrophobic property, and should maintain sufficient toughness and strength, and still have a certain strength during the degradation process, etc., combined with other comprehensive factors, we believe that the addition of PDO monomer ratio should be between 20% and 40%, and its mechanical properties and hydrophobic properties can meet the requirements of rectal implantation. Within this range, the anastomotic stent has a certain hydrophobicity, and the mechanical properties are very stable in dry and wet states, maintaining a certain mechanical strength and also having excellent flexibility, which ensures that it meets the strength without foreign body sensation and discomfort, and can be used as a good carrier for repairing tissues in intestinal trauma. Therefore, with P (TMC-co-PDO) random copolymer as the main base material, by adding rigid biodegradable polymers for formulation, the anastomotic stent can have good toughness, maintain a certain mechanical strength within two weeks after implantation in the body, and minimize the deformation of the cavity while the body is degraded.
[0049] This patent subsequently selected a sample with a PDO monomer addition ratio of 7:3 as the main substrate of the anastomotic stent, compounded it with at least one of PLA, PCL, and PBS, and electrospun it to prepare an intestinal anastomotic stent with a special structure and morphology.
[0050] Table 4. Different blending ratios of P(TMC-co-PDO) copolymers and PLA, PCL, and PBS and their mechanical properties after spinning
[0051]
[0052] Technical personnel should note that although the present invention has been described according to the above specific implementation methods, the inventive concept of the present invention is not limited to this invention, and any modification using the inventive concept will be included in the scope of protection of this patent.
[0053] The above is only a preferred embodiment of the present invention, and the protection scope of the present invention is not limited to the above embodiments. All technical solutions under the concept of the present invention belong to the protection scope of the present invention. It should be pointed out that for ordinary technicians in this technical field, some improvements and modifications without departing from the principle of the present invention should also be regarded as the protection scope of the present invention.
Claims
1. An intestinal flexible anastomotic stent, comprising a tubular stent body (1), wherein the stent body (1) comprises a side wall, characterized in that The upper and lower ends of the stent body (1) are respectively an inlet end (11) and an outlet end (12); a boss (2) is provided on the annular upper edge of the inlet end (11); the lower edge of the outlet end (12) is a concave polygonal structure; each dominant angle (3) of the lower edge of the concave polygonal structure forms an inwardly folded fold structure (31) on the side wall of the stent body (1); the lower edge of the concave polygonal structure is deformed by force to reduce the dominant angle (3); the stent body is made of a bio-flexible elastomer, which is a blend of a P (TMC-co-PDO) copolymer and at least one of PLA, PCL, and PBS; the addition ratio of TMC and PDO in the P (TMC-co-PDO) copolymer is 9:1-6:4, and the blending ratio of at least one of PLA, PCL, and PBS is 5-20%.
2. The intestinal flexible anastomotic stent according to claim 1, characterized in that: The stent body (1) comprises a suture portion, wherein the suture portion comprises a non-recommended angle (3) side of an annular upper edge of the inlet end (11) and a lower edge of a concave polygonal structure of the outlet end (12).
3. The intestinal flexible anastomotic stent according to claim 1, characterized in that: The length of the pleated structure (31) is 1 / 2-2 / 3 of the height of the support body (1).
4. The intestinal flexible anastomotic stent according to claim 3, characterized in that: The thickness of the inner wall of the bracket body (1) is 0.20-0.6 mm.
5. The intestinal flexible anastomotic stent according to claim 4, characterized in that: The thickness of the side wall at the fold structure (31) is smaller than the thickness of the side wall above the fold structure (31).
6. The intestinal flexible anastomotic stent according to claim 1, characterized in that: The pleated structure (31) is an arc-shaped groove structure that is shallow at the top and deep at the bottom, and the deepest depth of the bottom of the arc-shaped groove is 0.4-0.8 mm.
7. The intestinal flexible anastomotic stent according to claim 1, characterized in that: The intestinal flexible anastomotic stent is prepared by the following steps: (1) Synthesis of P(TMC-co-PDO) copolymer: In an anhydrous and oxygen-free environment, 90-60wt% TMC monomer, 10-40wt% PDO and 1-5wt% catalyst Sn(Oct)2 solution were added to a reaction tube. A magnet was placed in the reaction tube to ensure that the reaction tube was anhydrous and oxygen-free. The tube mouth was sealed with silicone grease to ensure that no oxygen and water could enter. The reaction tube was placed in an oil bath for reaction at a temperature of 120-150°C for 24-48 hours. After the reaction was completed, the tube was taken out for use. (2) Dissolution of P(TMC-co-PDO): Dissolve the P(TMC-co-PDO) copolymer with CHCl3, DMF or THF at a solid-liquid ratio of 1:
5. First, wash the inner wall with CHCl3, DMF or THF several times to wash away the silicone grease and unreacted monomers. Then add excess CHCl3, DMF or THF and place on a shaker with the shaker temperature set at 37°C until the solution is completely dissolved. (3) Purification of P(TMC-co-PDO): The dissolved solution was slowly poured into a beaker filled with n-hexane for purification. The mixture was slowly poured in and stirred continuously. The obtained flocculent P(TMC-co-PDO) was filtered and then vacuum dried for 48 h. (4) Preparation of electrospinning solution: P(TMC-co-PDO) copolymer and at least one of PLA, PCL and PBS were compounded and added to the solvent DMF / THF, where DMF:THF=1:1, and placed in a constant temperature shaker at 37°C for 24 hours until completely dissolved. After complete dissolution, electrospinning was performed; (5) Preparation of anastomotic tube by electrospinning: The intestinal flexible anastomotic stent according to any one of claims 1 to 6 is obtained by electrospinning on an electrospinning device, wherein the parameter setting range is as follows: voltage (-5, 30) V; needle pushing speed V = 1.0 ~ 5.0 ml / h; roller speed V = 100 ~ 500 RPM; temperature T = 25 ~ 35 ° C; humidity WET = 20 ~ 40%.
Citation Information
Patent Citations
BAN-based (body area network-based) dairy cow sign monitoring device
CN103230265A
Novel intestinal anastomosis ring
CN109480943A
Intestinal tract protective sleeve
CN213606587U
Flexible anastomosis stent for intestinal tract
CN216495452U
Visceral tissue approximating method and device
US20110098732A1